A study on electroplating / Saidatulakmar Shamsuddin - Shamsuddin, Saidatulakmar (Universiti Teknologi MARA, Perlis, 2003)
Electroplating is one of the process that is used in the semiconductor industry to prevent base metal from oxidation and to provide an easily solder able surface for soldering of component onto printed circuit board. The problem in electroplating is studied and the optimum parameter to yield the quality product is the main purpose of this study. The result shows that a substantial improvement can be achieved by the standard parameter.